(untitled) (Horizontes de Enfermería, 2020)
In this research, nutritional risk factors predisposing to cardiovascular diseases (CVD) in adults and adolescents from Chalguayacu province of Imbabura were determined. It is a qualitative and quantitative, descriptive, cross-sectional study. A semi-structured survey was applied to obtain information on sociodemographic characteristics, evaluate nutritional status and body composition; for which the data and measurements of weight, height, and waist contour were taken. In adults, the main results refer that; 79.10% were in the range of 20 - 59 years, the vast majority (72.7%) are overweight + obese, 66.7% have excess fat, and these indicators are more prevalent in women with a significant association between obesity and high-fat percentage. In adolescents, 14.3% are overweight + obese and excess fat comprises 8.2%. According to the predictor index of cardiovascular risk waist/height, 72.14% of adults are under this condition and 8.2% of adolescents. In addition, one in four Afro-descendants declares that they have high blood pressure, and more than half report a family history of hypertension and diabetes. The perception of body weight was also significantly different from the actual nutritional status. In conclusion, based on these indicators, adults rate their health status as regular while adolescents rate it as good, as the study determined the presence of nutritional cardiovascular risk factors in this population.